When can legacy soil data be used, and when should new data be collected instead? - Hendriks, C.M.J.; Stoorvogel, J.J.; Lutz, F.; Claessens, Lieven (Elsevier, 2019)
Soil data requirements and soil data acquisition tools and techniques have changed over recent decades. In general, soil scientists can: i) collect new data in the field and ignore the data that are available, ii) rely entirely on legacy soil data or iii) combine available legacy data with new data collection. This study aims to analyse and discuss the choices soil scientists make to balance between the use of legacy soil data and the collection of new soil data. A literature review on soil data acquisition was carried out and illustrated that the use of legacy soil data is still often very limited, while soil data availability increased over recent decades. Studies that use legacy soil data often use conventional soil data, which are criticised in literature. A regional and local case study was carried out to illustrate the choices that have to be made for obtaining the required soil data. It turned out that both case studies preferred to combine new soil data collection and legacy soil data. Many of the reviewed studies could reduce their sampling effort by making better use of available data, tools and techniques. Besides, soil scientists can help facilitating soil data acquisition by developing soil data warehouses.